Динаміка перерозподілу навантажень на осі автобуса колісної схеми 6х2 при гальмуванні - Дуфанець, Ігор (ТзОВ «Галицька видавнича спілка», 2021)
The article describes the redistribution of the load on the axle when braking on an ultra-large threeaxle bus with air suspension and two adjacent.
Dynamic of load distribution on bus axles with 6x2 wheel scheme when braking
Keywords: 656.13